Towards comprehensive mental health care: experiences and challenges of psychosocial care in Brazil - Mariá Lanzotti Sampaio; José Patrício Bispo Júnior (BMC, 2021)
Abstract Background Recommendations are in place for mental health (MH) care to be developed into a comprehensive, people-centred perspective and organised primarily through community services. In recent decades, Brazil has promoted psychiatric reform aimed at transforming the hospital-centred model into a psychosocial model of MH. However, current political and economic changes threaten this reform. This article analyses the comprehensive MH care offered by a Psychosocial Care Network (Rede de Atenção Psicossocial - RAPS) in Brazil. Methods The study involved semi-structured in-depth interviews with 33 stakeholders (policymakers, health professionals, and MH service users) and direct observation of MH services members of the RAPS. Data were analysed using framework analysis with the following dimensions: mental health services access, long-term mental health care, comprehensive mental health care, and crisis patient care. Results Results indicated progression towards comprehensive MH care provision. We identified MH care provided primarily by community services, featuring an 'open door' policy, development of localised actions and a search for autonomy. Deinstitutionalisation principles and the psychosocial model support a comprehensive view of MH by policy makers, MH professionals, and users. However, difficulties in providing comprehensive care remain, with the main challenges being insufficient services offered and difficulties in user access at all levels of care, fragile integration between services, lack of clear definitions of the responsibilities of each service, discontinuity of care, limitations in family support, and fragility in crisis patient care. Conclusion We highlight the need to increase funding and services of RAPS, qualification of staff professional, family support, and development of strategies for integrating services. Support and expansion of MH care depend on strengthening the Brazilian health system, which is in danger of being dismantled.